Design Error Management: Interaction of People, Organization and the Project Environment in Construction - Love, Peter; Lopez, Robert; Kim, J. (Taylor & Francis Group, 2014)
Design errors can have a negative impact on the cost, schedule and safety performance of construction projects. They can also have an adverse effect on an organisation’s profitability, as additional work requires resources and time to rectify the error that has occurred. The reduction (i.e. measures designed to limit the occurrence of failures) and containment (i.e. measures designed to increase the detection and accelerate the recovery of errors) of design errors can therefore ameliorate organisational and project performance as well as improve safety. A systemic framework that classifies design error reduction and containment strategies according to people, organisation and project is propagated. It is suggested that when people, organisational and project strategies are implemented, incongruence then the propensity for design error reductionwill significantly increase. The proposed framework can be used as a point for reference for implementing error management strategies to anticipate for ‘what might go wrong’ in construction projects.